2014
DOI: 10.2319/120213-888.1
|View full text |Cite
|
Sign up to set email alerts
|

The perception of facial asymmetry using 3-dimensional simulated images

Abstract: Perception of asymmetry is affected by the amount of asymmetry and the observer group, with orthodontists being more critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 10 publications
1
28
1
Order By: Relevance
“…All facial characteristics perceived differently by both genders. Males perceived "facial symmetry" and "facial vertical proportions" more precisely than females did although this is contradictory to the results reported by McAvincheya et al 10 and Soni et al 7 which indicated that gender of the observer had no influence on perception of "facial symmetry" and "facial vertical proportions", respectively. This contradiction might be due to the difference in the level of dental experience of the raters as in their study the rater were either laypersons or orthodontists.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…All facial characteristics perceived differently by both genders. Males perceived "facial symmetry" and "facial vertical proportions" more precisely than females did although this is contradictory to the results reported by McAvincheya et al 10 and Soni et al 7 which indicated that gender of the observer had no influence on perception of "facial symmetry" and "facial vertical proportions", respectively. This contradiction might be due to the difference in the level of dental experience of the raters as in their study the rater were either laypersons or orthodontists.…”
Section: Discussioncontrasting
confidence: 66%
“…Many studies evaluated laypersons' and/or dental specialist perception of specific facial esthetic characters including "facial profile", 6 "facial vertical proportions" 7,8 and "facial symmetry". 9,10 In line with that, a recent systematic review 11 sought to summarize studies that assessed laypersons' and/or dental professionals' perception of different facial esthetic parameters; they search for articles evaluated facial esthetic parameters including facial profile, facial height, facial symmetry and profile lip position. So far, there has not been a study that evaluated the perception of the most important facial characteristics; facial symmetry, facial profile and facial vertical proportions collectively by laypersons and different dental professionals.…”
Section: Introductionmentioning
confidence: 99%
“…More than two thirds of the dental students perceived symmetric or 2 mm facial asymmetry, McAvinchey et al 13 found that dental students considered 5.13 ± 2.06 mm of facial asymmetry is normal. We found that there is no sex difference in perception of facial asymmetry; this is similar to the findings of McAvinchey et al 13 Facial profile is the most important and standardized soft tissue parameter used in orthodontic practice. 14 Assessment of soft tissue facial profile revealed that about 95% of the participating dental students consider slightly convex and straight profiles, respectively, as pleasant, with no sex difference.…”
Section: Discussionmentioning
confidence: 99%
“…Perception of facial asymmetry is important to clinicians in assessment and treatment and to patients themselves as part of normal required esthetics. More than two thirds of the dental students perceived symmetric or 2 mm facial asymmetry, McAvinchey et al found that dental students considered 5.13 ± 2.06 mm of facial asymmetry is normal. We found that there is no sex difference in perception of facial asymmetry; this is similar to the findings of McAvinchey et al…”
Section: Discussionmentioning
confidence: 99%
“…20 Anthropologic studies regard symmetry as an important factor that makes the face appear attractive, 8,9,[21][22][23][24][25][26][27][28][29] and symmetry can affect various methods of facial recognition. 2 There have been many studies to evaluate facial asymmetry.…”
Section: Discussionmentioning
confidence: 99%